Besar Sampel dan Cara Pengambilan Sampel dalam Penelitian Kedokteran dan Kesehatan - DAHLAN, M Sopiyudin (Salemba Medika, 2010)
Besar Sampel dan Cara Pengambilan Sampel dalam Penelitian Kedokteran dan ...